Method for hydrophobing cellulose nanofiber, and cellulose nanofiber hydrophobed body

By replacing hydroxyl groups of cellulose nanofibers with carbonyl or carboxylic acid groups, the method addresses the contamination issues of TEMPO-based hydrophobization, enhancing resin compatibility and mechanical properties without using halogen or ionic substances.

JP2025011909APending Publication Date: 2025-01-24RESONAC CORP

Patent Information

Application Number
JP2023114325
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing methods for hydrophobizing cellulose nanofibers using TEMPO result in the contamination of halogen and ionic substances, leading to environmental and economic drawbacks, and limit their application in semiconductor materials due to the presence of these impurities.

Method used

A method involving the use of carbonyl group-containing monomers or carboxylic acid group-containing monomers, polar organic solvents, and catalysts to replace the hydroxyl groups of cellulose nanofibers without halogen or ionic substances, resulting in a hydrophobic cellulose nanofiber with diverse terminal substituents.

Benefits of technology

The method produces cellulose nanofibers that are highly compatible with resins, improving tensile strength and thermal stability, while eliminating the need for costly catalysts and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011909000009
    Figure 2025011909000009
  • Figure 2025011909000010
    Figure 2025011909000010
  • Figure 2025011909000011
    Figure 2025011909000011
Patent Text Reader

Abstract

To provide a method for hydrophobing a cellulose nanofiber which can obtain a cellulose nanofiber hydrophobed body rich in variation in a structure of a hydrophobic part without using a substance containing a halogen element and an ionic substance, and an excessive amount of a raw material in a cellulose nanofiber.SOLUTION: A method for hydrophobing a cellulose nanofiber includes mixing and dispersing raw material components containing at least a cellulose nanofiber, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, a polar organic solvent, and a catalyst in the same system, and substituting a primary hydroxyl group of a cellulose molecule constituting the cellulose nanofiber by an organic group containing a carbonyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for hydrophobizing cellulose nanofibers, in which hydroxyl groups in cellulose nanofibers are hydrophobized by substituting them with organic compounds, and to a hydrophobized cellulose nanofiber. [Background technology]

[0002] In recent years, there has been a demand for lighter and smaller electronic materials such as semiconductors, optical materials, and capacitors in order to improve capacity and increase lamination, and there is also a demand for lighter, smaller, and thinner films to be used in these materials (see Patent Document 1). In addition, there is also a demand for lighter automotive materials to improve fuel efficiency and driving range, and there is a demand for various resins used in automotive materials to be lighter and stronger at the same time (see Patent Document 2).

[0003] There is a demand for various films and resins to be thinner, smaller, and lighter, but it is not easy to achieve such thinning, miniaturization, and lighter weight while maintaining mechanical properties such as tensile strength and toughness.

[0004] 2. Description of the Related Art In recent years, attention has been focused on a technique for incorporating reinforcing fibers into a resin or film as a way of achieving both improved mechanical strength and reduced thickness and weight of various films and resins.

[0005] Reinforcing fibers include cellulose nanofibers, glass fibers, carbon fibers, and aramid fibers, and by incorporating a certain amount of any of these into a resin or film, the mechanical strength can be improved.

[0006] Among these, cellulose nanofibers are organic compounds, so if they can be uniformly dispersed and dissolved in resins and films, they can prevent defects in appearance. In addition, cellulose nanofibers have the properties of high electrical insulation and a low coefficient of linear expansion (hereinafter also referred to as CTE), so they are expected to be used in components that require insulation or measurability. Furthermore, when recycling resins and films containing reinforcing fibers, after they are scrapped, only cellulose nanofibers, which are organic compounds, can be automatically sorted using near-infrared rays among the reinforcing fibers described above, which has the advantage of being environmentally friendly (see Non-Patent Document 1).

[0007] For the above reasons, in recent years, there has been active research into incorporating cellulose nanofibers into resins and films to improve their properties (see Patent Document 3). However, due to the amphiphilicity of the hydroxyl groups in the cellulose molecules that make up the cellulose nanofibers, the cellulose molecules form hydrogen bonds with each other to produce aggregates of cellulose nanofibers, making them less compatible with, dispersible in, and bonded to organic compounds such as resins. Therefore, it is preferable to hydrophobize the hydroxyl groups on the outside of the cellulose molecules in advance.

[0008] The most widely used method for hydrophobizing cellulose nanofibers is the chemical fiberization method, in which the hydroxyl groups of cellulose nanofibers are carbonyl ionized using an oxidizing agent such as 2,2,6,6-tetramethyl-1-piperidine-N-oxy radical (hereinafter abbreviated as TEMPO), and then hydrophobized to form a carboxylic acid with a proton added, or hydrophobized by various functional group conversions (see Patent Document 4).

[0009] The advantage of the hydrophobicity method using chemical fiberization with TEMPO is that the fiber units of the cellulose nanofibers are ionized, causing them to repel each other and inhibiting hydrogen bonds between the fibers, resulting in fibers in which each bundle is finely fiberized. Since the surface area is increased by finely fiberizing the fibers, good dispersibility is obtained when the fibers are impregnated into resins or films, and a significant improvement in functionality is observed.

[0010] However, disadvantages of the hydrophobization method using TEMPO include the fact that TEMPO itself is as expensive as or more expensive than precious metal catalysts, and even if only a small amount of catalyst is used, it will increase the price of the cellulose nanofiber material. In addition, in order to activate TEMPO, a co-catalyst material containing halogens or sodium is required, and therefore the cellulose nanofiber material also contains ions such as halogens and sodium. In addition, purification using large amounts of water is required to recover and wash TEMPO after the reaction is complete, which is disadvantageous in terms of price, environmental impact, and productivity.

[0011] In some cases, after hydrophobization using TEMPO, the material is washed with a large amount of aqueous solution to remove the halogens; however, the aqueous solution used often contains ions that trap the halogens, and even if the halogens are removed, the cellulose nanofiber material still ends up containing ionic substances, which is an issue.

[0012] If cellulose nanofiber material contains halogens or ionic substances, it becomes difficult to use it as a semiconductor material. Therefore, even if cellulose nanofibers can be defibrated, hydrophobized, and dispersed or incorporated into resins or films, there will be limitations to their applications.

[0013] Furthermore, when cellulose nanofibers are hydrophobized using TEMPO, the only terminal substituent that contributes to hydrophobization can be a carboxyl group, resulting in a lack of structural variety.

[0014] There have also been several reported cases in which cellulose nanofibers have been chemically defibrated and hydrophobized using materials that do not use TEMPO. For example, a method in which an excess amount of a base and an acid anhydride is reacted with cellulose nanofibers, or a method in which a halogenated ester is reacted with cellulose nanofibers to hydrophobize them, are known (see Patent Document 5).

[0015] However, the hydrophobization method described in Patent Document 5 had problems such as the use of an excessive amount of raw material in the reaction with the cellulose nanofibers containing ionic substances such as halogens. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] International Publication No. 2018 / 056459 [Patent Document 2] JP 2019-151782 A [Patent Document 3] JP 2022-159126 A [Patent Document 4] International Publication No. 2010 / 116794 [Patent Document 5] International Publication No. 2017 / 073700 [Non-patent literature]

[0017] [Non-Patent Document 1] Tamaki Kojima, Panasonic Technical Journal, 57, 1, (2011) Summary of the Invention [Problem to be solved by the invention]

[0018] In order to disperse, dissolve, and incorporate cellulose nanofibers into resins or films, it is preferable to hydrophobize the hydroxyl groups of the cellulose nanofibers and prevent hydrogen bonding and the formation of aggregates between the cellulose nanofibers. However, the above-mentioned conventional hydrophobization methods have problems such as the inclusion of halogens and ions in the cellulose nanofiber material after hydrophobization, the high cost and high production process, which are industrially disadvantageous, and the need for large amounts of materials and wastewater treatment, which are environmentally disadvantageous.

[0019] The present invention has been made in consideration of the above-mentioned problems in the conventional art, and its object is to provide a method for hydrophobizing cellulose nanofibers that does not use substances containing halogen elements or ionic substances, does not use excessive amounts of raw materials relative to the cellulose nanofiber, and can produce hydrophobized cellulose nanofibers with a wide variety of structures in the hydrophobized portion, and to provide hydrophobized cellulose nanofibers that are highly compatible with resins. [Means for solving the problem]

[0020] Through careful investigation, the inventors have discovered a formulation that does not use halogens or ionic substances in cellulose nanofibers, and does not use excessive amounts of raw materials relative to the cellulose nanofibers, and have developed a new hydrophobization method for hydrophobizing the hydroxyl groups of cellulose nanofibers. That is, one aspect of the present invention that solves the above problems is as follows.

[0021] (1) A method for hydrophobizing cellulose nanofibers, comprising mixing and dispersing raw material components containing at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, a polar organic solvent, and a catalyst in the same system, and replacing the primary hydroxyl groups of the cellulose molecules constituting the cellulose nanofibers with organic groups containing a carbonyl group.

[0022] (2) The method for hydrophobizing cellulose nanofibers according to (1) above, wherein the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is at least one selected from the group consisting of aliphatic ring-opened carboxylic acids, aliphatic acid anhydrides, aliphatic acid dianhydrides, aromatic acid anhydrides, aromatic acid dianhydrides, and bis-aromatic acid dianhydrides.

[0023] (3) The method for hydrophobizing cellulose nanofibers according to (1) or (2), in which the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is used in an amount of 1 to 100 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

[0024] (4) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (3), wherein the catalyst is at least one selected from the group consisting of organic base catalysts, Bronsted acid catalysts, and metal catalysts.

[0025] (5) The method for hydrophobizing cellulose nanofibers according to (4) above, wherein the catalyst is used in an amount of 0.01 to 0.5 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

[0026] (6) The method for hydrophobizing cellulose nanofibers according to (4) or (5), wherein the organic base catalyst is a nitrogen-containing organic compound.

[0027] (7) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (6), wherein the raw material components further contain a base.

[0028] (8) The method for hydrophobizing cellulose nanofibers according to (7) above, wherein the base is a nitrogen-containing organic compound.

[0029] (9) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (8), wherein the cellulose nanofibers are a cellulose nanofiber solution obtained by solvent-substitution of an aqueous dispersion of cellulose nanofibers having a non-volatile content of 10% by mass or less with a polar organic solvent.

[0030] (10) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (9), wherein the cellulose nanofibers have a fiber diameter of 1 to 1000 nm, and the hydrophobized cellulose nanofibers have a fiber diameter of 1 to 300 nm.

[0031] (11) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (10), wherein the raw material components do not contain any halogen-containing substances, cation-containing substances, or anion-containing substances.

[0032] (12) A hydrophobized cellulose nanofiber represented by the following general formula (II): [ka] [In general formula (II), R represents an alkyl group or an aliphatic or aromatic carboxylic acid group, each of which may have a substituent. n represents an integer of 10 to 500,000.] Effect of the Invention

[0033] According to the present invention, it is possible to provide a method for hydrophobizing cellulose nanofibers that does not use substances containing halogen elements or ionic substances, and does not use excessive amounts of raw materials relative to the cellulose nanofiber, and that can produce hydrophobized cellulose nanofibers with a wide variety of structures in the hydrophobized portion, as well as hydrophobized cellulose nanofibers that are highly compatible with resins. [Brief description of the drawings]

[0034] [Figure 1] FIG. 2 shows the infrared absorption spectrum of the hydrophobized cellulose nanofiber obtained in Example 1. [Diagram 2] FIG. 1 shows the infrared absorption spectrum of the hydrophobized cellulose nanofiber obtained in Example 11. [Diagram 3] FIG. 1 shows an infrared absorption spectrum of the hydrophobized cellulose nanofiber obtained in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] <Method for making cellulose nanofibers hydrophobic> The method for hydrophobizing cellulose nanofibers of this embodiment is characterized by mixing and dispersing raw material components containing at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, and a polar organic solvent in the same system, and replacing the primary hydroxyl groups of the cellulose molecules that make up the cellulose nanofibers with organic groups that contain a carbonyl group.

[0036] In the method for hydrophobizing cellulose nanofibers of this embodiment, at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, and a polar organic solvent are used as raw material components. That is, cellulose nanofibers can be hydrophobized without using a substance containing a halogen element or an ionic substance. In addition, since there is no need to use an expensive catalyst such as TEMPO, it is possible to realize hydrophobization of cellulose nanofibers at low cost. Furthermore, when hydrophobizing using TEMPO, the only substituent at the end is a carboxyl group, but in this embodiment, there are many types of substituent at the end that contribute to hydrophobization, and there is a wide variety in structure. In addition, in this embodiment, the hydroxyl groups held by the cellulose nanofibers can be hydrophobized using cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer in an amount equivalent to the amount of the substance of the cellulose nanofiber, and a catalyst and a solvent in an amount less than the amount of the substance of the cellulose nanofiber.

[0037] Without being bound by theory, by hydrophobizing the hydroxyl groups of cellulose nanofibers, it is possible to suppress the action of hydrogen bonding and aggregation between cellulose nanofiber units via the hydroxyl groups, making it easier to disperse and dissolve in various resins and varnishes. Furthermore, when cellulose nanofibers are dispersed and dissolved in resins and varnishes, even if the diameter of the cellulose nanofibers reaches about 1000 nm, the cellulose nanofiber material can fully exert a network effect when used in resins and varnishes or when made into films, thereby improving tensile strength and elastic modulus. Similarly, it can also be effective in suppressing thermal expansion.

[0038] By dispersing or dissolving the hydrophobic cellulose nanofibers obtained by this embodiment in any resin or varnish and coating or molding the resulting material, the tensile strength and elastic modulus of a film or molded product made from the original resin or varnish can be improved by 1.5 times or more.Similarly, by dispersing or dissolving the hydrophobic cellulose nanofibers obtained by this embodiment in any resin or varnish and coating or molding the resulting material, the thermal expansion coefficient of a film or molded product made from the original resin or varnish can be reduced by 20% or more.

[0039] The fiber diameter of the hydrophobic cellulose nanofiber obtained by this embodiment can be 1 to 300 nm. Although the fiber diameter of cellulose nanofibers hydrophobized using conventional catalysts can be as small as about 5 nm, the hydrophobic cellulose nanofiber obtained by this embodiment has the same dispersibility and compatibility with resins as conventional hydrophobic cellulose nanofibers, even if the fiber diameter is larger.

[0040] Below, we will first explain the cellulose nanofibers in the raw material components used in the method for hydrophobizing cellulose nanofibers of this embodiment, and the structure of the resulting hydrophobized cellulose nanofibers, and then explain the other raw material components.

[0041] [Cellulose nanofiber] The cellulose polymer that constitutes the cellulose nanofiber used as the raw material is represented by the following general formula (I).

[0042] [ka] [In general formula (I), n represents an integer of 10 to 100,000.]

[0043] The type of cellulose nanofiber used in this embodiment is not particularly limited, but pulp or cellulose nanofibers defibrated from pulp can be used. In order to efficiently react with various organic materials, the cellulose nanofibers are preferably defibrated products. Furthermore, mechanically defibrated products can be used as defibrated products of cellulose nanofibers.

[0044] Cellulose nanofibers generally contain moisture, and the moisture concentration may reach 99% by mass (there is no problem with mechanically defibrated cellulose nanofibers as long as the non-volatile content is 1% by mass or more). If the hydrophobic cellulose nanofiber obtained according to this embodiment is dispersed in a solvent, it can be processed into a film by solvent coating or the like, so the raw cellulose nanofiber may also be, for example, an aqueous dispersion mechanically defibrated from pulp.

[0045] On the other hand, a step of replacing the water contained in the cellulose nanofiber with any organic solvent and dehydrating the cellulose nanofiber may be provided before carrying out the hydrophobization reaction. That is, in this embodiment, a cellulose nanofiber solution obtained by replacing an aqueous dispersion of cellulose nanofibers with a non-volatile content of 10% by mass or less with a polar organic solvent can be used as the cellulose nanofiber. Usually, an aqueous dispersion of cellulose nanofibers mechanically defibrated from pulp has a moist creamy or paste-like appearance even when the non-volatile content of the cellulose nanofiber is about 5% by mass (water content is about 95%). Even in this case, there is no problem as long as the cellulose nanofibers can be uniformly dispersed in the solvent when diluted with an organic solvent and subjected to solvent replacement (dehydration).

[0046] When replacing the water contained in cellulose nanofibers with any polar organic solvent, the cellulose nanofibers are first dispersed and dissolved in any organic solvent. The water originally contained in the cellulose nanofibers is then removed by distillation to obtain a cellulose nanofiber / organic solvent solution that does not contain water molecules. Without being bound by theory, it is believed that if cellulose nanofibers are heated and dehydrated alone without a distillation process, the molecules of the cellulose nanofibers will irreversibly aggregate via hydrogen bonds as they are dehydrated. It is also believed that dehydrating the water molecules allows the reactions to proceed more efficiently in subsequent processes because various materials are not hindered by the water molecules.

[0047] The non-volatile content of the cellulose nanofibers substituted and dispersed in a polar solvent used in this embodiment is not particularly limited, but may be 50% by mass or less, 5% by mass or less, 1% by mass or less, or 0.5% by mass or less. Generally, commercially available cellulose nanofibers have a non-volatile content of 5% by mass, so when substituted and dispersed in a solvent, the non-volatile content is often 5% by mass or less.

[0048] Next, the fiber diameter of the cellulose nanofiber used as the raw material will be described. The fiber diameter of the cellulose nanofiber used in the cellulose nanofiber-containing resin is not particularly limited, but may be 1 to 1000 nm or 5 to 500 nm. Without being bound by theory, it is believed that the smaller the fiber diameter, the less aggregation occurs due to hydrogen bonding between hydroxyl groups of the cellulose nanofiber, and the larger the surface area becomes, which increases the efficiency of hydrophobizing the hydroxyl groups of the cellulose nanofiber.

[0049] Various definitions of the fiber diameter of cellulose nanofibers have been proposed by various research institutes and papers, but in this embodiment, the maximum central fiber diameter of a single cellulose fiber is 1 μm or less, and the branched portion of the fiber includes a fiber diameter of 1 to 50 nm. The method for measuring the fiber diameter of cellulose nanofibers will be described later.

[0050] The fiber length of the cellulose nanofibers used in this embodiment is not particularly limited, but may be 100 nm or more, 500 nm or more, 1000 nm (1 μm) or more, or 1,000,000 nm (1 mm) or more. Without being bound by theory, it is expected that the longer the fiber length, the more the mesh-like networking will progress in the resin or film to which it is added, and the tensile strength of the molded product or film will improve.

[0051] On the other hand, the hydrophobized cellulose nanofiber obtained by the present embodiment is represented by the following general formula (II).

[0052] [ka] [In general formula (II), R represents an alkyl group or an aliphatic or aromatic carboxylic acid group, each of which may have a substituent. n represents an integer of 10 to 100,000.]

[0053] In the general formula (II), n is the repeating number of the monomer in [ ] and represents an integer of 10 to 500,0000, preferably 100 to 100,000, and more preferably 1000 to 100,000. The same applies to n in the above-mentioned general formula (I).

[0054] [Polar solvent] The polar solvent used in this embodiment is preferably a solvent in which the cellulose nanofibers disperse when the water molecules in the cellulose nanofibers are replaced with an organic solvent by distillation. The polar solvent is not particularly limited, but is preferably a solvent with a boiling point higher than that of water. Examples include nitrogen-containing solvents such as N-methyl-2-pyrrolidone (N-methylpyrrolidone), N,N'-dimethylacetamide, N,N'-dimethylformamide, 2-vinylpyridine, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidine; sulfur-containing solvents such as dimethyl sulfoxide, diethyl sulfoxide, dimethyl sulfone, ethyl methyl sulfone, and sulfolane; ether-based solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and triethylene glycol diethyl ether; and ester-based solvents such as γ-butyrolactone and cellosolve acetate.

[0055] [Carbonyl group-containing monomers, carboxylic acid group-containing monomers] In this embodiment, when hydrophobizing cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer is used as a hydrophobizing reactant to be substituted with a hydroxyl group. Examples of the carbonyl group-containing monomer include acetic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, pyromellitic anhydride, carbonyl diphthalic anhydride, trimellitic anhydride, cyclohexane tetracarboxylic anhydride, tetrahydrophthalic anhydride, norbornene phthalic anhydride, octenyl succinic anhydride, dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, and 4,4'-oxydiphthalic anhydride. Examples of the carboxylic acid group-containing monomer include monomers containing a group derived from a carboxylic acid such as succinic acid, propionic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, 1,9-nonanedicarboxylic acid, dodecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, octadecanedioic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, decahydro-1,4-naphthalenedicarboxylic acid, (1a,2a,4a)-1,2,4-cyclohexanetricarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, phthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and acenaphthylene-5,6-dicarboxylic acid. Among them, the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is preferably one selected from the group consisting of aliphatic ring-opening carboxylic acids, aliphatic acid anhydrides, aliphatic acid dianhydrides, aromatic acid anhydrides, aromatic acid dianhydrides, and bis-aromatic acid dianhydrides. From the viewpoint of improving heat resistance, those having an aromatic group, such as phthalic acid and terephthalic acid, are preferred.

[0056] In this embodiment, the primary hydroxyl groups of the cellulose molecules constituting the cellulose nanofibers are replaced with carbonyl group-containing monomer residues or carboxylic acid group-containing monomer residues. As described above, when cellulose nanofibers are hydrophobized using TEMPO, the only terminal substituent that contributes to hydrophobization is the carboxyl group. In contrast, in this embodiment, the terminal substituents differ depending on the carbonyl group-containing monomer or carboxylic acid group-containing monomer used, resulting in a wide variety of structures.

[0057] The blending amount (mass ratio) of the carbonyl group-containing monomer or carboxylic acid group-containing monomer as the hydrophobization reactant for the cellulose nanofiber is preferably 1 to 100 parts by mass, more preferably 1 to 50 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the total of the cellulose nanofiber and the polar organic solvent. Without being bound by theory, when the amount of the hydrophobization reactant is large, there is a concern that unreacted acid anhydride or carboxylic acid remains in the system and cannot be completely removed by post-treatment. In addition, when the hydrophobized cellulose nanofiber obtained by this embodiment is used to further carry out a reaction by functional group conversion (when carrying out amidation, imidization, urethanization, olefin addition, etc.), there is also a concern that the remaining acid anhydride or carboxylic acid may induce a side reaction.

[0058] [catalyst] In this embodiment, the raw material component preferably further contains at least one catalyst selected from the group consisting of an organic base catalyst, a Bronsted acid catalyst, and a metal catalyst. Without being bound by theory, it is expected that the electrophilicity of the hydrophobization reactant is increased by activating the catalyst by coordinating with the carbonyl group-containing monomer or the carboxylic acid group-containing monomer, which is the hydrophobization reactant, and the substitution with the hydroxyl group of the cellulose nanofiber will progress more efficiently. The catalyst is not particularly limited as long as it has a coordination effect with the carbonyl, but it is preferable to use an organic base catalyst, a Bronsted acid catalyst, or a metal catalyst. However, in order to prevent the incorporation of halogens or ionic substances into the reaction system, it is preferable to select a non-halogen, non-ionic substance as the catalyst. Examples of Bronsted acid catalysts include sulfuric acid, p-toluenesulfonic acid, and methanesulfonic acid. Examples of the organic base catalyst include 4-dimethylaminopyridine, 1,8-diazabicyclo[5,4,0]undecene-7, 1,5-diazabicyclo[4,3,0]nonene-5, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, methyltriamylammonium hydroxide, methyltributylammonium hydroxide, etc. As the organic base catalyst, nitrogen-containing organic compounds such as amine compounds are preferred. Examples of metal catalysts include zinc acetate (II), zinc nitrate (II), zinc carbonate (II), cobalt acetate (II), cobalt hydroxide (II), cobalt nitrate (II), cobalt sulfate (II), cobalt carbonate (II), boric acid, isobutylboronic acid, phenylboronic acid, 1-naphthaleneboronic acid, tetra-i-propoxytitanium, antimony trioxide, triphenylantimony, triphenylantimony diacetate, dibutyltin, dibutyltin bis, sodium hydrogen carbonate, etc. These may be used alone or in combination of two or more.

[0059] The amount (mass ratio) of the catalyst to the cellulose nanofibers is preferably 0.01 to 0.5 parts by mass, and more preferably 0.1 to 0.4 parts by mass, per 100 parts by mass of the total of the cellulose nanofibers and the polar organic solvent. Without being bound by theory, if the amount of catalyst is too small, the efficiency of hydrophobization decreases, while if the amount of catalyst is too large, there is a concern that side reactions such as homopolymerization of the hydrophobization reaction product may occur.

[0060] [base] In this embodiment, it is preferable that the raw material components further contain a base. Although not bound by theory, it is expected that the base activates the protons of the hydroxyl groups of the cellulose nanofibers, thereby improving the reactivity of the cellulose nanofibers. Examples of bases include pyridine, triethylamine, 1,4-diazabicyclo[2,2,2]octane, N-ethyldiisopropylamine, 2,6-dimethylpyridine, tetramethylammonium hydroxide, sodium ethoxide, potassium-t-butoxide, lithium diisopropylamide, potassium hexamethyldisilazide, and the like. These may be used alone or in combination of two or more. In addition, although these are not particularly limited, it is more preferable to use an amine compound (nitrogen-containing organic compound) from the viewpoint of preventing the inclusion of alkaline ionic substances.

[0061] The amount (mass ratio) of the base to the cellulose nanofiber is preferably 0 to 100 parts, and more preferably 1 to 50 parts, based on the mass equivalent of the cellulose nanofiber. Without being bound by theory, the hydrophobization reaction proceeds even in the absence of a base, but the incorporation of a base can activate the hydroxyl groups of the cellulose nanofiber, thereby improving the efficiency of hydrophobization.

[0062] In this embodiment, it is preferable that one or both of the organic base catalyst and the base are nitrogen-containing organic compounds, since no halogen or ionic substance is used.

[0063] The above raw material components can be prepared so as not to contain halogen-containing substances, cation-containing substances, or anion-containing substances. Therefore, the hydrophobized cellulose nanofiber obtained by this embodiment can be used for applications such as semiconductor materials where contamination with halogens or ionic substances is to be avoided.

[0064] In this embodiment, an example of the process for hydrophobizing cellulose nanofibers is a process in which a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, a polar organic solvent, a catalyst, and a base are appropriately selected and mixed into a cellulose nanofiber solution that has been solvent-substituted as described above, and then the mixture is poured into a sealed flask container, etc. By adjusting the stirring and temperature and allowing the reaction to proceed at an appropriate time, a hydrophobic cellulose nanofiber can be obtained.

[0065] When the cellulose nanofibers are hydrophobized, the reaction temperature may be room temperature or may be heated. When the cellulose nanofibers are heated, the reaction temperature may be 40° C. or higher and 250° C. or lower, or 40° C. or higher and 200° C. or lower. Although not bound by theory, since there is a risk that the cellulose nanofibers will decompose or aggregate at high temperatures, the reaction temperature is preferably 250° C. or lower, and more preferably 200° C. or lower.

[0066] In addition, when hydrophobizing the cellulose nanofibers, it is preferable to produce the cellulose nanofibers while stirring the reaction solution. The stirring speed is not particularly limited, but may be 50 rpm to 10,000 rpm, 100 rpm to 7,500 rpm, or 250 rpm to 5,000 rpm. Although not bound by theory, by stirring the cellulose nanofibers in a solution, the fiber units of the cellulose nanofibers are defibrated, and the aggregation of the fiber units can be suppressed. In addition, by improving the dispersibility and preventing the aggregation of the fiber units, the surface area of ​​the cellulose nanofibers is increased, and it is expected that the efficiency of hydrophobization will be improved.

[0067] The reaction time for hydrophobizing the cellulose nanofibers may be from 5 hours to 48 hours, from 10 hours to 36 hours, or from 15 hours to 24 hours.

[0068] The gas in the reaction system when hydrophobizing the cellulose nanofibers is not particularly limited, and may be air or an inert atmosphere such as nitrogen.

[0069] It is preferable to seal the reaction vessel when hydrophobizing the cellulose nanofibers. When heating the flask vessel, it is possible to place a Dimroth condenser on the top of the flask vessel, but it is preferable to plug the top of the Dimroth condenser. This is to prevent water molecules from coordinating and adhering to the hydrophobized cellulose nanofibers due to the inclusion of excess air from the outside.

[0070] The hydrophobic cellulose nanofiber obtained by this embodiment is dispersed in an organic solvent, and therefore the obtained organic solvent dispersion can be used as is when it is desired to use it as a raw material for further functional group conversion, when it is desired to mix and disperse it with other varnish materials, or when it is desired to form it into a film by solvent coating.

[0071] When it is desired to recover the hydrophobized cellulose nanofibers obtained by this embodiment as a solid content, the method is not particularly limited, and desolvation and recovery of the solid content of the hydrophobized cellulose nanofibers can be carried out by existing methods, such as a method of recovering the hydrophobized cellulose nanofibers remaining on filter paper by suction filtration, a method of volatilizing the solvent using a pressure reducing device such as an evaporator, and a method of using a centrifuge.

[0072] When resin molding or film coating is carried out using a resin in which cellulose nanofibers substituted with any hydrophobic group obtained by this embodiment are dispersed, dissolved, or impregnated, a material is obtained that does not produce holes, bumps, or cracks, compared to resin moldings or films impregnated with cellulose nanofibers that have not been hydrophobized.

[0073] When a resin obtained by this embodiment in which cellulose nanofibers substituted with any hydrophobic group are dispersed, dissolved, or impregnated is used to coat a resin molding or film, the tensile strength is improved by 1.5 times or more compared to a resin molding or film impregnated with cellulose nanofibers that have not been hydrophobized, and is improved by 2 times or more compared to a resin molding or film not impregnated with cellulose nanofibers at all.

[0074] When a resin obtained by this embodiment in which cellulose nanofibers substituted with any hydrophobic group are dispersed, dissolved, or impregnated is used to coat a resin molding or film, the coefficient of linear expansion (hereinafter referred to as "CTE") is reduced by 20% or more compared to a resin molding or film impregnated with cellulose nanofibers that have not been hydrophobized. In addition, when the CTE is compared to a resin molding or film not impregnated with cellulose nanofibers at all, it is reduced by 50% or more.

[0075] Cellulose nanofibers substituted with arbitrary hydrophobic groups obtained by the hydrophobization method of this embodiment can reduce the cost of the hydrophobization process to 1 / 10 of that of cellulose nanofibers obtained by conventional hydrophobization methods, and can also reduce the levels of ions such as halogens and sodium contained in the cellulose nanofibers to below the detection limit.

[0076] Furthermore, since the hydrophobic group terminal of the hydrophobic cellulose nanofiber obtained by this embodiment is an ester group or a carboxylic acid group, a functional group substitution reaction can be further performed after carrying out the synthesis treatment of hydrophobization. For example, amidation, imidation, urethanization, olefin addition, etc. are possible, and this can impart the properties of each functional group to the cellulose nanofiber material, thereby achieving further high functionality. The catalyst system used in the synthesis method of the hydrophobic cellulose nanofiber obtained by this embodiment can also be used for functional group conversion such as amidation, imidation, urethanization, and olefin addition. Therefore, in this case, since a process such as catalyst removal and washing is not required after hydrophobizing the cellulose nanofiber, an industrially advantageous method can be provided in terms of cost and work.

[0077] <Analysis method of hydrophobized cellulose nanofibers according to the present embodiment> The hydrophobic cellulose nanofibers obtained by the method for hydrophobizing cellulose nanofibers according to the present embodiment can be analyzed by a Fourier transform infrared spectrophotometer (FT-IR). The infrared absorption wavelength of the carbonyl derived from the ester group and carboxylic acid group generated by the hydrophobization is measured at 1700 cm -1 In addition, if the hydrophobicization process for cellulose nanofibers is carried out in a closed system and the entire process from preparation to analysis is carried out in a manner that prevents water from entering from the outside, the hydrophobicity of the cellulose nanofibers can be confirmed at 3500 cm -1 A decrease in the infrared absorption wavelength of the hydroxyl group (-OH) can be confirmed before and after hydrophobization. Although some water molecules that could not be removed from the cellulose nanofiber and adsorption of water molecules in the reaction vessel are considered to be involved, if the hydrophobization process is progressing, the primary hydroxyl groups, which account for one-third of the hydroxyl groups in the cellulose nanofiber, are substituted and hydrophobized, and the 3500 cm -1 It can be seen that the infrared absorption wavelength area of ​​the hydroxyl group (-OH), which can be seen before and after, is reduced by about 1 / 3.

[0078] <Method for analyzing fiber diameter of hydrophobic cellulose nanofiber> When analyzing the fiber diameter of the hydrophobized cellulose nanofiber obtained by the cellulose nanofiber hydrophobization method according to the present embodiment, a scanning electron microscope (SEM) can be used, although the analysis method is not limited thereto. When analyzing a sample using SEM, it is usually necessary to collect the sample as a solid and dry the solid sample to volatilize the solvent and water contained in the sample, but the sample can be obtained by an existing method. For example, as described in the examples described later, the hydrophobized cellulose nanofiber after production can be collected on a filter paper by suction filtration, and then dried in a heating dryer at 60°C for about 2 hours to obtain the sample. Although not bound by theory, cellulose nanofibers may irreversibly aggregate due to high-temperature heating or rapid heating, and the fiber diameter may become thicker than immediately after production, so heating is preferably at 100°C for 2 hours or less, more preferably at 80°C for 2 hours or less, and more preferably at 60°C for 2 hours or less.

[0079] The fiber diameter of the dried sample of the hydrophobized cellulose nanofiber obtained as described above can be analyzed by observing it with an SEM.

[0080] <Solvent replacement of cellulose nanofiber aqueous dispersion> As described above, when an aqueous dispersion of cellulose nanofibers mechanically defibrated from pulp is used as a raw material, it is preferable to dehydrate the cellulose nanofibers and disperse them in an organic solvent. An example of solvent replacement for an aqueous dispersion of cellulose nanofibers is shown below.

[0081] 10-50g of cellulose nanofiber water dispersion (Mori Machinery Corporation, Cell Film C-500, NV5%) is added to a 300mL separable flask, and 100-200g of dimethyl sulfoxide (DMSO) is added thereto, and then the separable flask is covered. A stirrer, thermometer, nitrogen inlet tube, fractionating tower, cooling tube, and distillate receiving flask are placed on the top of the flask to form a distillation apparatus, and then heated with a mantle heater or oil bath. The temperature inside the flask is set to 100-130°C, and heating and stirring are performed for 3-10 hours. The process is completed when the theoretical amount of water coordinated to or contained in the cellulose nanofibers is collected in the distillate flask. The cellulose nanofiber solvent dispersion remaining in the separable flask is collected and used as the cellulose nanofiber raw material before hydrophobization.

[0082] Furthermore, the cellulose nanofiber raw material obtained as described above can be further defibrated by stirring it in a high-pressure homogenizer at 10,000 rpm for 10 to 30 minutes, or by subjecting it to ultrasonic treatment in an ultrasonic homogenizer for 10 to 30 minutes.

[0083] Alternatively, a solvent dispersion of defibrated cellulose nanofibers can be obtained and used as is. Also, cellulose nanofiber pulp can be used to hydrophobize the cellulose nanofibers by replacing the hydroxyl groups.

[0084] By appropriately replacing the aqueous dispersion of cellulose nanofibers with an organic solvent, it is possible to prepare a cellulose nanofiber dispersion solution that is easily dispersed and compatible with resins and varnishes.Furthermore, by appropriately using a catalyst on the cellulose nanofibers, it is possible to replace the hydroxyl groups of the cellulose nanofibers with acid anhydrides or carboxylic acids to hydrophobize the cellulose nanofibers, thereby providing hydrophobic cellulose nanofibers dispersed in an organic solvent.

[0085] <Post-treatment of hydrophobic cellulose nanofibers> When the obtained hydrophobic cellulose nanofibers are in the form of a solution, they can be used as is without post-treatment, such as by forming them into a film or mixing them into a resin solution. When purifying the simple substance through post-treatment, the solvent, catalyst, and remaining unreacted hydrophobic reaction products can be filtered by suction filtration to recover the simple substance on filter paper. In this case, the purity of the hydrophobic cellulose nanofibers can be improved by repeatedly washing with a general-purpose solvent. After filtration, the recovered hydrophobic cellulose nanofibers can be dried in a dryer at 60°C for 2 hours to remove the solvent used for washing.

[0086] <Evaluation of hydrophobicity of hydrophobic cellulose nanofibers by FT-IR analysis> The degree of hydrophobization of the hydrophobized cellulose nanofiber material obtained according to this embodiment can be evaluated using FT-IR analysis as follows. After the reaction is complete, the solution is separated from the hydrophobic cellulose nanofibers by filtration. At this time, by filtration while washing with any organic solvent with a boiling point of 80°C or less, the remaining carboxylic acid group-containing monomer in the solution, the catalyst, the base, and the solvent contained in the cellulose nanofibers can be transferred to the filtrate side. Since the presence or absence of carbonyl groups can be confirmed later by FT-IR analysis, it is preferable to use an organic solvent that does not contain carbonyl groups or ketone groups. Next, the solid cellulose nanofibers separated by filtration are transferred to a heat-resistant container and placed in a 60°C dryer for 1 hour to volatilize the solvent contained in the cellulose nanofibers. Without being bound by theory, in order to dry efficiently, it is preferable to transfer the cellulose nanofibers to a metal petri dish or the like and spread them thinly to increase the surface area. In addition, heating to 100°C or above or heating for 3 hours or more may cause the cellulose nanofibers to irreversibly aggregate. Finally, the dried cellulose nanofibers are analyzed using FT-IR analysis. At this time, the cellulose nanofibers before the hydrophobization reaction are also dried in the same manner as above, and the degree of hydrophobization is evaluated by comparison as follows. The evaluation criteria are shown in the examples below.

[0087] <Hydrophobic cellulose nanofiber> The hydrophobized cellulose nanofiber of this embodiment is characterized by being represented by the following general formula (II).

[0088] [ka] [In general formula (II), R represents an alkyl group or an aliphatic or aromatic carboxylic acid group, each of which may have a substituent. n represents an integer of 10 to 100,000.]

[0089] The hydrophobized cellulose nanofibers of this embodiment are obtained by the above-mentioned method for hydrophobizing cellulose nanofibers of this embodiment. It is presumed that the hydrophobized cellulose nanofibers have a higher degree of hydrophobization than the hydrophobized cellulose nanofibers obtained using TEMPO as a catalyst. This is because the hydrogen atoms of the primary hydroxyl groups of the cellulose molecules in the hydrophobized cellulose nanofibers of this embodiment are replaced with carbonyl group-containing monomer residues or carboxylic acid group-containing monomer residues, and the carbonyl group-containing monomer residues or carboxylic acid group-containing monomer residues are bonded via methylene groups and oxygen atoms, resulting in a bulky structure. Therefore, the steric hindrance that occurs between the cellulose nanofiber units can suppress the hydrogen bonding and aggregation action via the hydroxyl groups. In contrast, the hydrophobized cellulose nanofibers obtained using TEMPO as a catalyst are inferior in bulkiness because the carboxyl groups are directly bonded to the carbon atoms that constitute the six-membered rings of the cellulose molecules, and it is presumed that the hydrophobization caused by the steric hindrance is inferior.

[0090] Furthermore, the hydrophobized cellulose nanofibers of this embodiment are represented by the above general formula (II), and since R is diverse, there is a wide variety of structures.

[0091] In general formula (II), the alkyl group represented by R may be an alkyl group having 1 to 10 carbon atoms. The aliphatic carboxylic acid group represented by R may be an aliphatic carboxylic acid group having 1 to 20 carbon atoms, and the aromatic carboxylic acid group represented by R may be an aromatic carboxylic acid group having 7 to 50 carbon atoms. In the case where the alkyl group, the aliphatic carboxylic acid group, and the aromatic group have a substituent, examples of the substituent include an amino group, an ester group, an ether group, and a urethane group.

[0092] In the general formula (II), an example of R is -C x H (2x+1) , -C m H (2x+1) COOH, -CHCOOH, -C x H (2x+1) CONHC y H (2y+1) NH2, -C6H4CONHC y H (2y+1) Here, x is an integer of 1 to 10, and y is an integer of 1 to 20.

[0093] Other features of the hydrophobized cellulose nanofibers of this embodiment have been described in the above-mentioned method for hydrophobizing cellulose nanofibers, so description thereof will be omitted here.

[0094] The hydrophobized cellulose nanofiber of this embodiment can be added to an adhesive film for semiconductors. By adding the hydrophobized cellulose nanofiber to an adhesive film for semiconductors, it tends to be possible to reduce the coefficient of linear expansion (CTE) and increase the thixotropy. EXAMPLES

[0095] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to the following examples. In the following, "parts" such as "0.02 parts of acetic anhydride" refers to "parts by mass."

[0096] [Example 1] The substance constituting the general formula (I) of the cellulose nanofiber was adjusted to a non-volatile content of 0.5% by mass using dimethyl sulfoxide (hereinafter referred to as "DMSO") as a solvent according to the method shown in "Solvent replacement of cellulose nanofiber aqueous dispersion" above, and dehydrated, dispersed in the solvent, and defibrated. The defibrated material was used as a cellulose raw material liquid. 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, and 0.02 parts of acetic anhydride, 0.001 parts of 4-dimethylaminopyridine (DMAP), and 0.5 parts of pyridine were added to the cellulose raw material liquid, and the separable flask was closed to form a reaction system. The reaction liquid was stirred at room temperature for 24 hours at 250 rpm to obtain a solution of cellulose nanofibers (R = CH3 in the general formula (II)) in which an acyl group (methyl ester group) derived from acetic anhydride was substituted.

[0097] [Example 2] In the same manner as in Example 1, 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that 0.001 parts of 1,8-diazabicyclo[5,4,0]undecene-7 (DBU) was added as a catalyst instead of 4-dimethylaminopyridine (DMAP), and a solution of hydrophobized cellulose nanofiber (R = CH3 in the above general formula (II)) was obtained.

[0098] [Example 3] In the same manner as in Example 1, 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that 0.001 parts of 1,5-diazabicyclo[4,3,0]nonene-5 (DBN) was added as a catalyst instead of 4-dimethylaminopyridine (DMAP), and a solution of hydrophobized cellulose nanofiber (R = CH3 in the above general formula (II)) was obtained.

[0099] [Example 4] A hydrophobization reaction was carried out in the same manner as in Example 1, except that 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, and 0.001 parts of 4-dimethylaminopyridine (DMAP) and 0.001 parts of 1,5-diazabicyclo[4,3,0]nonene-5 (DBN) were added as catalysts, and the amount of acetic anhydride was changed to 0.004 parts. A solution of hydrophobized cellulose nanofibers (R = CH3 in the above general formula (II)) was obtained.

[0100] [Example 5] In the same manner as in Example 1, 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that the amount of 4-dimethylaminopyridine (DMAP) as a catalyst was changed to 0.003 parts, and a solution of hydrophobized cellulose nanofiber (R = CH3 in the above general formula (II)) was obtained.

[0101] [Example 6] In the same manner as in Example 1, 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that the amount of pyridine was changed to 0.25 parts, and a solution of hydrophobized cellulose nanofiber (R = CH3 in the above general formula (II)) was obtained.

[0102] [Example 7] When preparing a solvent-dispersed cellulose raw material liquid using the method described above in "Solvent replacement of cellulose nanofiber aqueous dispersion," N-methylpyrrolidone (NMP) was used as the solvent instead of DMSO. After that, a hydrophobization reaction was carried out using the same composition and method as in Example 1, and a solution of hydrophobized cellulose nanofibers (R=CH3 in the above general formula (II)) was obtained.

[0103] [Example 8] When preparing a solvent-dispersed cellulose raw material liquid using the method described above in "Solvent replacement of cellulose nanofiber aqueous dispersion," cyclohexanone (CHN) was used as the solvent instead of DMSO. After that, a hydrophobization reaction was carried out using the same composition and method as in Example 1, and a solution of hydrophobized cellulose nanofibers (R=CH3 in the above general formula (II)) was obtained.

[0104] [Example 9] In the same manner as in Example 1, 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that the reaction temperature was increased from room temperature to 100°C, and a solution of hydrophobized cellulose nanofiber (R = CH3 in the above general formula (II)) was obtained.

[0105] [Example 10] In the same manner as in Example 1, 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that 0.02 parts of succinic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and a solution of hydrophobized cellulose nanofiber (R = C2H4COOH in the above general formula (II)) was obtained.

[0106] [Example 11] A hydrophobization reaction was carried out in the same manner as in Example 1, except that 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, 0.004 parts of succinic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and 0.001 parts of 4-dimethylaminopyridine (DMAP) and 0.001 parts of 1,8-diazabicyclo[5,4,0]undecene-7 (DBU) were added as catalysts, and a solution of hydrophobized cellulose nanofiber (R = C2H4COOH in the above general formula (II)) was obtained.

[0107] [Example 12] A hydrophobization reaction was carried out in the same manner as in Example 1, except that 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and 0.02 parts of maleic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and 0.5 parts of triethylamine was added instead of pyridine, to obtain a solution of hydrophobized cellulose nanofibers (R = C2H2COOH in the above general formula (II)).

[0108] [Example 13] A hydrophobization reaction was carried out in the same manner as in Example 1, except that 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, 0.02 parts of succinic acid was added instead of acetic anhydride as the hydrophobization reactant, and the amount of 4-dimethylaminopyridine (DMAP) as the catalyst was changed to 0.003 parts, and a solution of hydrophobized cellulose nanofibers (R = C2H4COOH in the above general formula (II)) was obtained.

[0109] [Example 14] In the same manner as in Example 1, 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, and 0.02 parts of sebacic acid were placed in place of acetic anhydride as a hydrophobization reactant, and the amount of 4-dimethylaminopyridine (DMAP) as a catalyst was changed to 0.003 parts. A hydrophobization reaction was carried out in the same manner as in Example 1, and a hydrophobized cellulose nanofiber (R = CH in the above general formula (II)) was obtained. 16 A solution of 1,2-dichlorophenyl (COOH) was obtained.

[0110] [Example 15] In the same manner as in Example 1, 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that 0.02 parts of phthalic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and a solution of hydrophobized cellulose nanofiber (R = CHCOOH in the above general formula (II)) was obtained.

[0111] [Example 16] A hydrophobization reaction was carried out in the same manner as in Example 1, except that 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, 0.02 parts of phthalic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and 0.001 parts of 4-dimethylaminopyridine (DMAP) and 0.001 parts of 1,8-diazabicyclo[5,4,0]undecene-7 (DBU) were added as catalysts, and a solution of hydrophobized cellulose nanofibers (R = CHCOOH in the above general formula (II)) was obtained.

[0112] [Example 17] In the same manner as in Example 1, 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and a hydrophobization reaction was carried out using the same composition and method as in Example 1, except that 0.02 parts of pyromellitic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and a solution of hydrophobized cellulose nanofiber (R = C6H2(COOH)3 in the above general formula (II)) was obtained.

[0113] [Example 18] In the same manner as in Example 1, 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, and 0.02 parts of pyromellitic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and 0.001 parts of 4-dimethylaminopyridine (DMAP) and 0.001 parts of 1,8-diazabicyclo[5,4,0]undecene-7 were added as catalysts. The hydrophobization reaction was carried out in the same manner as in Example 1, and a solution of hydrophobized cellulose nanofiber (R = CH(COOH) in the above general formula (II)) was obtained.

[0114] [Example 19] A hydrophobization reaction was carried out in the same manner as in Example 1, except that 10 g of cellulose raw material liquid was placed in a 100 mL separable flask, 0.02 parts of oxydiphthalic anhydride was added instead of acetic anhydride as a hydrophobization reactant, and 0.001 parts of 4-dimethylaminopyridine (DMAP) and 0.001 parts of 1,8-diazabicyclo[5,4,0]undecene-7 were added as catalysts, and a solution of hydrophobized cellulose nanofiber (R = CH(COOH) in the above general formula (II)) was obtained.

[0115] [Comparative Example 1] In the same manner as in Example 1, 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, and the hydrophobization reaction was promoted using the same composition and method as in Example 1, except that no catalyst was used.

[0116] [Comparative Example 2] Instead of 10 g of cellulose raw material liquid, 10 g of commercially available cellulose pulp (Nippon Paper Industries Co., Ltd., dissolving pulp (DP)) was placed in a 1 L container, and 50 parts of acetic anhydride and 50 parts of pyridine were added relative to the mass of cellulose. The mixture was stirred in a mixer rotor at room temperature for 24 hours to obtain hydrophobic cellulose nanofibers.

[0117] [Comparative Example 3] Following the method described above in "Solvent replacement of cellulose nanofiber aqueous dispersion," the non-volatile content was adjusted to 0.5 mass% using DMSO as a solvent, and the cellulose nanofibers in a non-hydrophobic state that had been dehydrated and dispersed in the solvent were evaluated.

[0118] <Evaluation> 1. Fiber diameter The fiber diameter of the hydrophobic cellulose nanofibers obtained in each of the Examples and Comparative Examples was measured according to the above-mentioned "Method for Analyzing Fiber Diameter of Hydrophobic Cellulose Nanofibers." The measurement results are shown in Tables 1 to 3.

[0119] 2.Resin dispersibility The hydrophobized cellulose nanofibers obtained in each Example and Comparative Example were added to an aliphatic acrylic resin and a bisphenol A type epoxy resin at 1% by mass, and evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 1 to 3. Without being bound by theory, it is known that cellulose nanofibers are incompatible with other resin solutions and aggregate without exhibiting dispersibility because the numerous hydroxyl groups present in the molecules form hydrogen bonds with each other. [Evaluation Criteria] 〇: Good dispersibility When it is compatible with both aliphatic acrylic resins and bisphenol A type epoxy resins, and no aggregation or precipitation is observed. ×: Poor dispersibility If aggregation or precipitation is observed in either aliphatic acrylic resin or bisphenol A type epoxy resin. Without being bound by theory, if a material exhibits dispersibility in both aliphatic acrylic resin, which has a relatively low polarity among resins, and bisphenol A type epoxy resin, which has a relatively high polarity among resins, it can be expected that the material will also exhibit dispersibility in other resins.

[0120] 3.Hue The hue of the dispersion of hydrophobized cellulose nanofibers obtained in each Example and Comparative Example was judged by visual inspection. If the color was the same white color as after the solvent replacement before the hydrophobization reaction, it was rated as "white," and if it was black, it was rated as "black." The results are shown in Tables 1 to 3. If the hydrophobic structure deteriorates (decomposes), the material may turn yellow or black. Also, if the cellulose skeleton deteriorates (decomposes) due to the materials added during the hydrophobic reaction, the material may turn yellow or black. Therefore, a white color is preferable.

[0121] 4. Glass transition temperature (Tg) In each of the Examples and Comparative Examples, measurements were performed using a DSC differential scanning calorimeter (Rigaku Thermo Plus DSC 8230) with carrier gas air (normal pressure), heating conditions: 30 to 300°C (initial temperature 30°C), heating rate 10°C / min, and a sample weight of 3 mg packed into an aluminum pan for DSC. The glass transition point of the hydrophobic cellulose nanofibers observed in response to heating was then measured. The measurement results are shown in Tables 1 to 3.

[0122] 5. Hydrophobicity In each of the Examples and Comparative Examples, after the reaction was completed, the solution and the hydrophobized cellulose nanofibers were separated by filtration. The solid hydrophobized cellulose nanofibers separated by filtration were transferred to a heat-resistant container and placed in a dryer heated to 60°C for 1 hour to volatilize the solvent contained in the hydrophobized cellulose nanofibers. The dried hydrophobized cellulose nanofibers were then analyzed using FT-IR analysis. At this time, the cellulose nanofibers before the hydrophobization reaction were also dried in the same manner as above, and the hydrophobization degree was evaluated by comparison as follows. The evaluation results are shown in Tables 1 to 3. Note that for Examples 1 and 11 and Comparative Example 4, the infrared absorption spectra by FT-IR analysis are shown in Figures 1 to 3, respectively. [Evaluation Criteria] 〇:3500cm -1 The peak area of ​​the hydroxyl group stretching before and after the reaction is reduced compared to before the reaction, and the peak area of ​​the hydroxyl group stretching before and after the reaction is reduced compared to before the reaction. -1 The peak area ratio of the carbonyl stretching occurring before and after reached more than 1% compared with the total area ratio. △:3500cm -1 The peak areas of the hydroxyl group stretching before and after the reaction did not change compared to before the reaction, but the peak areas of the hydroxyl group stretching -1 The peak area ratio of the carbonyl stretching occurring before and after reached more than 0.1% compared with the total area ratio. ×:3500cm -1 The peak area of ​​the hydroxyl group stretching before and after the reaction did not change compared to before and after the reaction, and the peak area of ​​the hydroxyl group stretching after the reaction did not change compared to before and after the reaction. -1 The peak area ratio of the carbonyl stretching occurring before and after was less than 0.1% compared to the total area ratio.

[0123] [Table 1]

[0124] [Table 2]

[0125] [Table 3]

[0126] In Tables 1 to 3, CNF-OH / DMSO indicates the cellulose raw material liquid treated by the method shown in Example 1 using DMSO as the polar organic solvent.

[0127] It can be seen from Tables 1 to 3 that the hydrophobic cellulose nanofibers obtained in Examples 1 to 19 all had excellent dispersibility in resin and a high degree of hydrophobization. Furthermore, none of the raw material components in Examples 1 to 19 contained components containing halogens or ionic substances, and the obtained hydrophobic cellulose nanofibers did not contain halogens or ionic substances. In contrast to this, all of Comparative Examples 1 to 3 were poor in both dispersibility in the resin and degree of hydrophobicity.

Claims

1. A method for hydrophobizing cellulose nanofibers, comprising mixing and dispersing raw material components containing at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, a polar organic solvent, and a catalyst in the same system, and replacing the primary hydroxyl groups of the cellulose molecules constituting the cellulose nanofibers with organic groups containing a carbonyl group.

2. 2. The method for hydrophobizing cellulose nanofibers according to claim 1, wherein the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is at least one selected from the group consisting of aliphatic ring-opened carboxylic acids, aliphatic acid anhydrides, aliphatic acid dianhydrides, aromatic acid anhydrides, aromatic acid dianhydrides, and bis-aromatic acid dianhydrides.

3. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is used in an amount of 1 to 100 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

4. 3. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the catalyst is at least one selected from the group consisting of organic base catalysts, Bronsted acid catalysts, and metal catalysts.

5. The method for hydrophobizing cellulose nanofibers according to claim 4, wherein the catalyst is used in an amount of 0.01 to 0.5 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

6. The method for hydrophobizing cellulose nanofibers according to claim 4 , wherein the organic base catalyst is a nitrogen-containing organic compound.

7. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the raw material components further contain a base.

8. The method for hydrophobizing cellulose nanofibers according to claim 7 , wherein the base is a nitrogen-containing organic compound.

9. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the cellulose nanofibers are a cellulose nanofiber solution obtained by solvent-substitution of an aqueous dispersion of cellulose nanofibers having a non-volatile content of 10% by mass or less with a polar organic solvent.

10. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the fiber diameter of the cellulose nanofibers is 1 to 1000 nm, and the fiber diameter of the hydrophobized cellulose nanofibers is 1 to 300 nm.

11. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the raw material components do not contain any halogen-containing substances, cation-containing substances, or anion-containing substances.

12. A hydrophobized cellulose nanofiber represented by the following general formula (II): 【Chemistry 1】 [In general formula (II), R represents an alkyl group or an aliphatic or aromatic carboxylic acid group, each of which may have a substituent. n represents an integer of 10 to 500,000.]

Citation Information

Patent Citations

  • Thermoplastic resin composition, molding, automobile component, and method for producing thermoplastic resin composition

    JP2019151782A

  • Resin composition and method for producing the same

    JP2022159126A

  • Method for recovery / reuse of n-oxyl compound

    WO2010116794A1

  • Modified cellulose fine fibers and method for producing same

    WO2017073700A1

  • Method for producing polyamide

    WO2018056459A1

Cited By

  • Modified cellulose for improving stability of coating as well as preparation method and application of modified cellulose

    CN118165128A